2012
DOI: 10.4314/ijbcs.v6i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Effets des rhizobactéries PGPR sur le rendement et les teneurs en macroéléments du maïs sur sol ferralitique non dégradé au Sud-Bénin

Abstract: Effets des rhizobactéries PGPR sur le rendement et les teneurs en macroéléments du maïs sur sol ferralitique non dégradé au Sud-Bénin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…One of the convincing alternatives to ensure the self-sufficiency food production of the population is the intensive of the cereal cultures among the corn. In Benin, the maize represents the major crop in all agroecological zones (Adjanohoun et al, 2012). It remains the first cereal produced and consumed in Benin, far in front of the sorghum (Sorghum bicolor) and rice (Oriza spp.…”
Section: Introductionmentioning
confidence: 99%
“…One of the convincing alternatives to ensure the self-sufficiency food production of the population is the intensive of the cereal cultures among the corn. In Benin, the maize represents the major crop in all agroecological zones (Adjanohoun et al, 2012). It remains the first cereal produced and consumed in Benin, far in front of the sorghum (Sorghum bicolor) and rice (Oriza spp.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported the increase of maize yield [10,11], Tea [12], soybeans [13], alfalfa [14], wheat [15], and onion [16] simply by PGPR inoculation.…”
Section: Introductionmentioning
confidence: 99%
“…That is why the application of these essential nutrients (nitrogen, phosphorus and potassium) plants in the form of chemical fertilizers is part of intensive agriculture. Adjanohoun et al, [67] attributed the improvement of yields of corn achieved at the level of the plants inoculated with P. fluorescens, P. putida and A. lipoferum by increased absorption of nitrogen and potassium.…”
Section: Test In Greenhouse Conditionmentioning
confidence: 99%